The office of the constitutional judge in Sub-Saharan Africa : comparative study based on Benin, Gabonese and Malagasy examples - (:unkn) unknown (My University, 2021)
This thesis aims to reflect on the nature of the powers and duties devolved to constitutional judges in sub-Saharan Africa from the Benin, Gabonese and Malagasy examples. It is based on an assertion that is difficult to dispute : these judges exercise both jurisdictional and political powers and duties. In doing so, their office may seem banal, normal, standard in the sense that its hybrid character is the thing best shared by all constitutional courts. However, this is not the case because, if the office of these judges is standardized, it must be recognized that it is also unique. On the jurisdictional level, this singularization in standardization is attested by the fact that the High Courts follow a procedure identical to that of the ordinary judge and become administrative judges, when they control the constitutionality and legality of the administration's actions, and criminally judge them when they protect human rights. As a result, they create a new judicial order "in fact." Politically, the singularization in standardization is proven by the fact that the High Courts use their judicial power to appropriate not only the exercise of the legislative function, but also that of the constituent function. This political office can be interpreted differently. On the one hand, it would be inherent in the status and missions devolved to the constitutional judge of sub-Saharan Africa. On the other hand, it would be formidable because it changes not only the place of the judge in constitutional institutions, but also the acceptance of major constitutional principles such as the separation of powers and national sovereignty. In short, African constitutional judges exercise a hybrid office which, legal-political on form, is singular and standardized on the merits.
Keywords: African Research